Anti-scraping shading master batch and preparation method and application thereof, biodegradable composite material and preparation method and application thereof, biodegradable playing card and preparation method thereof
By using poly-butylene terephthalate-butylene adipate in biodegradable composite materials to prepare scratch-resistant masterbatches, the problem that existing materials cannot have both scratch-resistant and light-resistant effects is solved, and high-performance, low-cost and environmentally friendly material applications are achieved.
Patent Information
- Application Number
- CN202510063514.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing organic-inorganic material masterbatch cannot have good scratch resistance and light shading effects, and it is difficult to meet the dual needs of environmental protection and polymer material performance.
The combination of poly-butylene terephthalate-adipate, inorganic powder, dispersant, antioxidant, anti-ultraviolet agent, silicon material, bio-based sodium sulfonate, anti-hydrolyzer and pigment is used to prepare scratch-resistant light-shading masterbatches through the extrusion granulation process.
It has achieved anti-scratch and light-shielding masterbatch with excellent anti-scratch performance and light-shielding effect. It is suitable for biodegradable composite materials and playing cards and has the advantages of low-cost, environmental protection and industrial production.
Smart Images

Figure CN119875321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable materials, and in particular to an anti-scratch light-shielding masterbatch and a preparation method and application thereof, a biodegradable composite material and a preparation method and application thereof, and a biodegradable playing card and a preparation method thereof. Background Art
[0002] A large amount of white pollution (plastic products) and black pollution (rubber products) in nature are mainly caused by widely used polymer materials. With the increasing severity of environmental pollution, it is an inevitable trend to develop new degradable materials that are beneficial to environmental protection and have various properties of polymer materials. At present, degradable polymer materials mainly include microbial degradable materials, biodegradable materials, photodegradable materials and chemical degradable materials. Biodegradable materials that have excellent performance of polymer materials and can be completely decomposed and inorganic after being discarded have good application prospects. By adding organic-inorganic material masterbatch to biodegradable composite materials, the mechanical strength, degradability and processing properties of the material can be improved. However, the existing organic-inorganic material masterbatch cannot have good anti-scratch and light-shielding effects. Summary of the invention
[0003] In view of this, the object of the present invention is to provide an anti-scratch and light-shielding masterbatch and a preparation method and application thereof, a biodegradable composite material and a preparation method and application thereof, and a biodegradable playing card and a preparation method thereof. The anti-scratch and light-shielding masterbatch provided by the present invention has excellent anti-scratch and light-shielding effects.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides an anti-scratch light-shielding masterbatch, which comprises the following raw materials, measured by weight: 25 to 30 parts of polybutylene terephthalate-adipate, 40 to 80 parts of inorganic powder, 3 to 5 parts of dispersant, 0.2 to 1 part of antioxidant, 0.2 to 0.5 part of anti-ultraviolet agent, 5 to 16 parts of silicon material, 1 to 5 parts of bio-based sodium sulfonate, 3 to 5 parts of anti-hydrolysis agent and 0 to 5 parts of pigment.
[0006] Preferably, the number average molecular weight of the polybutylene terephthalate-adipate is 200,000 to 300,000;
[0007] The inorganic powder includes one or more of talc, calcium carbonate, barium sulfate and silicon powder; the particle size of the inorganic powder is ≤8 μm; the inorganic powder is activated before use, and the activation reagent used for the activation includes at least one of a coupling agent and stearic acid;
[0008] The dispersant includes one or more of oleamide, erucamide and ethylenebisstearamide;
[0009] The antioxidant includes one or more of phenolic antioxidants, amine antioxidants and phosphite antioxidants;
[0010] The silicon material includes at least one of ultra-high molecular weight organic silicon and potassium aluminum silicate;
[0011] The anti-hydrolysis agent includes at least one of monomeric polycarbodiimide and polymeric polycarbodiimide.
[0012] The present invention also provides a method for preparing the anti-scratch and light-shielding masterbatch described in the above technical solution, comprising the following steps: mixing the prepared raw materials and then extruding and granulating them to obtain the anti-scratch and light-shielding masterbatch.
[0013] The present invention also provides the use of the anti-scratch and light-shielding masterbatch described in the above technical solution or the anti-scratch and light-shielding masterbatch prepared by the preparation method described in the above technical solution as a filler.
[0014] The present invention also provides a biodegradable composite material, which comprises the following raw materials, measured by weight: 50 to 75 parts of polylactic acid, 0 to 10 parts of polyhydroxyalkanoate, 5 to 20 parts of polycaprolactone, 5 to 10 parts of polybutylene succinate, 5 to 20 parts of anti-scratch and light-shielding masterbatch, 1 to 5 parts of antistatic agent, 0 to 2 parts of rare earth additive, and 0 to 5 parts of pigment; the anti-scratch and light-shielding masterbatch is the anti-scratch and light-shielding masterbatch described in the above technical scheme or the anti-scratch and light-shielding masterbatch prepared by the preparation method described in the above technical scheme.
[0015] Preferably, the rare earth additive includes a lanthanide additive or a cerium additive;
[0016] The number average molecular weight of the polylactic acid is 150,000 to 300,000;
[0017] The number average molecular weight of the polycaprolactone is 60,000 to 80,000;
[0018] The number average molecular weight of the polybutylene succinate is 200,000 to 300,000;
[0019] The number average molecular weight of the polyhydroxyalkanoate is 400,000 to 600,000;
[0020] The polyhydroxyalkanoate includes one or more of poly-β-hydroxybutyric acid, poly 3-hydroxybutyrate / 4-hydroxybutyrate copolymer, poly-β-hydroxybutyric acid hexanoate and poly 3-hydroxybutyrate-co-3-hydroxyvalerate.
[0021] The present invention also provides a method for preparing the biodegradable composite material described in the above technical solution, comprising the following steps: mixing the raw materials for preparation, and performing melt extrusion granulation to obtain the biodegradable composite material.
[0022] The present invention also provides the use of the biodegradable composite material described in the above technical solution or the biodegradable composite material prepared by the preparation method described in the above technical solution in the preparation of playing cards, packaging materials or disposable blister products.
[0023] The present invention also provides a biodegradable playing card, which is made of the biodegradable composite material described in the above technical solution or the biodegradable composite material prepared by the preparation method described in the above technical solution.
[0024] The present invention also provides a method for preparing the biodegradable playing cards described in the above technical solution, comprising the following steps: mixing raw materials for preparing biodegradable composite materials, and sequentially performing sheet extrusion, stretching and shaping to obtain the biodegradable playing cards.
[0025] The present invention provides an anti-scratch light-shielding masterbatch, which comprises the following raw materials by weight: 25-30 parts of polybutylene terephthalate-adipate, 60-80 parts of inorganic powder, 3-5 parts of dispersant, 0.2-1 parts of antioxidant, 0.2-0.5 parts of anti-ultraviolet agent, 5-16 parts of silicon material, 1-5 parts of bio-based sodium sulfonate, 3-5 parts of anti-hydrolysis agent, and 0-5 parts of pigment. Under the joint action of polybutylene terephthalate-adipate, inorganic powder, dispersant, antioxidant, anti-ultraviolet agent, silicon material, bio-based sodium sulfonate, anti-hydrolysis agent and pigment, the anti-scratch light-shielding masterbatch has both excellent anti-scratch performance and light-shielding effect.
[0026] The method for preparing the anti-scratch light-shielding masterbatch provided by the invention has simple process, simple operation, low production cost, is green and environmentally friendly, and is suitable for industrial production.
[0027] The present invention also provides a biodegradable composite material, which comprises the following raw materials, measured by weight: 50-75 parts of polylactic acid, 8-10 parts of polyhydroxyalkanoate, 5-20 parts of polycaprolactone, 5-10 parts of polybutylene succinate, 5-20 parts of anti-scratch and light-shielding masterbatch, 1-5 parts of antistatic agent, 0-2 parts of rare earth additive, and 0-5 parts of pigment; the anti-scratch and light-shielding masterbatch is the anti-scratch and light-shielding masterbatch described in the above technical scheme or the anti-scratch and light-shielding masterbatch prepared by the preparation method described in the above technical scheme. The present invention uses polylactic acid as the main raw material to provide the basic hardness of the biodegradable composite material; adds polyhydroxyalkanoate to provide hardness and accelerate the degradation of polylactic acid after the material is used and discarded; adds polycaprolactone and polybutylene succinate to increase the flexibility and cold resistance of the anti-scratch light-shielding masterbatch; improves the scratch resistance of the surface of the biodegradable composite material and adjusts the light-shielding property of the material by the anti-scratch light-shielding masterbatch; reduces the static electricity generated in the production of the biodegradable composite material and the static electricity adsorption between sheets during printing by adding an antistatic agent; and helps to accelerate the shaping cycle of the biodegradable composite material during production and assists in improving the toughness of the biodegradable composite material by adding a rare earth additive. Moreover, the polylactic acid, polyhydroxyalkanoate, polycaprolactone and polybutylene succinate used in the present invention all have good printing adhesion. The biodegradable playing cards prepared by using the biodegradable composite material provided by the present invention as a preparation raw material have excellent antibacterial and anti-mildew properties, are low-carbon and environmentally friendly, are not easy to curl or open, are waterproof and moisture-proof, are easy to print, have good color fastness, have the texture of traditional paper, are completely biodegradable after use, or can be made into a household compost material as needed, and can replace traditional paper playing cards and PVC plastic playing cards. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a physical picture of the biodegradable playing cards prepared in Example 4. DETAILED DESCRIPTION
[0029] The invention provides an anti-scratch light-shielding masterbatch, which comprises the following raw materials, measured by weight: 25 to 30 parts of polybutylene terephthalate-adipate, 40 to 80 parts of inorganic powder, 3 to 5 parts of dispersant, 0.2 to 1 part of antioxidant, 0.2 to 0.5 part of anti-ultraviolet agent, 5 to 16 parts of silicon material, 1 to 5 parts of bio-based sodium sulfonate, 3 to 5 parts of anti-hydrolysis agent and 0 to 5 parts of pigment.
[0030] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0031] In terms of mass fraction, the raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 25 to 30 parts of polybutylene terephthalate-adipate (PBAT), which may be 25 parts, 25.5 parts, 26 parts, 26.5 parts, 27 parts, 27.5 parts, 28 parts, 28.5 parts, 29 parts, 29.5 parts or 30 parts in a specific embodiment. In the present invention, the number average molecular weight of the polybutylene terephthalate-adipate is preferably 200,000 to 300,000, which may be 200,000, 220,000, 250,000, 280,000 or 300,000 in a specific embodiment; the model of the polybutylene terephthalate-adipate preferably includes one or more of Xinjiang Lanshan Tunhe TH801, Kingfa Technology A400 and BASF C1200. The polybutylene terephthalate-adipate used in the present invention has good printing adhesion. The polybutylene terephthalate-adipate added in the present invention serves as a carrier material and toughening agent for the anti-scratch light-shielding masterbatch.
[0032] Based on the mass fraction of the polybutylene terephthalate-adipate, the raw materials for preparing the anti-scratch shading masterbatch provided by the present invention include 40 to 80 parts of inorganic powder, and in specific embodiments, it can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts or 80 parts. In the present invention, the inorganic powder preferably includes one or more of talcum powder, calcium carbonate, barium sulfate and silicon powder, and more preferably one or two of talcum powder and calcium carbonate; the particle size of the inorganic powder is preferably ≤8μm, and in specific embodiments, it can be nanometer-level or have a particle size of 5 to 8μm. The present invention can improve the shading performance of the anti-scratch shading masterbatch by adding inorganic powder, and the shading performance of the masterbatch is better after adding calcium carbonate.
[0033] In the present invention, the inorganic powder is preferably activated before use. Specifically, the inorganic powder is mixed with an activating agent and activated to obtain activated inorganic powder.
[0034] In the present invention, the activation reagent used in the activation preferably includes at least one of a coupling agent and stearic acid, and the coupling agent preferably includes one or more of an aluminate coupling agent, a titanate coupling agent and a silane coupling agent; the aluminate coupling agent preferably includes DL411; the titanate coupling agent preferably includes TCA-KTTS; the silane coupling agent preferably includes KH-550. In the present invention, the mass ratio of the inorganic powder to the activator is preferably 1:0.01-0.025, and in specific embodiments it can be 1:0.01, 1:0.011, 1:0.012, 1:0.013, 1:0.014, 1:0.015, 1:0.016, 1:0.017, 1:0.018, 1:0.019, 1:0.02, 1:0.021, 1:0.0222, 1:0.023, 1:0.024 or 1:0.025.
[0035] In the present invention, the activation temperature is preferably 25-40°C, and in a specific embodiment it can be 25°C, 30°C, 35°C or 40°C; the activation time is preferably 5-15min, and in a specific embodiment it can be 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min or 15min; the activation is preferably carried out under stirring conditions, and the stirring speed is preferably 400-800r / min, and in a specific embodiment it can be 400r / min, 500r / min, 600r / min, 700r / min or 800r / min; the activation is preferably carried out in a high mixer.
[0036] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 3 to 5 parts of a dispersant, based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, may be 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the dispersant preferably includes one or more of oleamide, erucic acid amide and ethylene bisstearic acid amide (EBS), and more preferably ethylene bisstearic acid amide.
[0037] Based on the mass fraction of the polybutylene terephthalate-adipate, the raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 0.2 to 1 parts of antioxidants, which can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts in specific embodiments. In the present invention, the antioxidant preferably includes one or more of a phenolic antioxidant and a phosphite antioxidant, more preferably a phenolic antioxidant and a phosphite antioxidant. The present invention has no special restrictions on the mass ratio of different antioxidants, and any ratio is acceptable. In the present invention, the phenolic antioxidant preferably includes antioxidant 1010. In the present invention, the phosphite antioxidant preferably includes antioxidant 168. In a specific embodiment of the present invention, the antioxidant is preferably a compound antioxidant of antioxidant 1010 and antioxidant 168, and the mass ratio of the antioxidant 1010 to the antioxidant 168 is preferably 1:1.
[0038] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 0.2 to 0.5 parts of an anti-ultraviolet agent based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, it can be 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts. In the present invention, the anti-ultraviolet agent preferably includes UV-3808.
[0039] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 5 to 16 parts of silicon material, based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, may be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts. In the present invention, the silicon material preferably includes at least one of ultra-high molecular weight organosilicon and potassium aluminum silicate, more preferably potassium aluminum silicate; the ultra-high molecular weight organosilicon preferably includes HG-600S. The potassium aluminum silicate used in the present invention has a special two-dimensional structure, which can significantly improve the anti-scratch performance of the masterbatch.
[0040] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 1 to 5 parts of bio-based sodium sulfonate based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, may be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the model of the bio-based sodium sulfonate preferably includes HG-600S. The present invention can increase the bio-based content of the anti-scratch light-shielding masterbatch by adding bio-based sodium sulfonate, and at the same time provide auxiliary lubrication for the inorganic powder material.
[0041] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 3 to 5 parts of an anti-hydrolysis agent, based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, may be 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the anti-hydrolysis agent preferably includes at least one of a monomeric polycarbodiimide and a polymeric polycarbodiimide, more preferably a polymeric polycarbodiimide; in a specific embodiment, the polymeric polycarbodiimide may be Shanghai Langyi 210. In the present invention, the anti-hydrolysis agent can react with PBAT to produce end-capping, thereby improving the weather resistance of the anti-scratch light-shielding masterbatch.
[0042] The raw materials for preparing the anti-scratch light-shielding masterbatch provided by the present invention include 0 to 5 parts of pigments, based on the mass fraction of the polybutylene terephthalate-adipate, and in specific embodiments, may be 0 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the pigment preferably includes one or more of titanium dioxide, lithopone, zinc white and antimony white; the titanium dioxide is preferably rutile titanium dioxide, and the rutile titanium dioxide used in the present invention will not yellow due to heat.
[0043] In the present invention, the particle size of the anti-scratch light-shielding masterbatch is preferably 2 to 3 mm, and in a specific embodiment may be 2 mm, 2.5 mm or 3 mm.
[0044] The present invention also provides a method for preparing the anti-scratch and light-shielding masterbatch described in the above technical solution, comprising the following steps: mixing the prepared raw materials and then extruding and granulating them to obtain the anti-scratch and light-shielding masterbatch.
[0045] In the present invention, the mixing preferably includes: first mixing bio-based sodium sulfonate, silicon material, dispersant and inorganic powder to obtain a mixture; second mixing the mixture, polybutylene terephthalate-adipate, antioxidant, anti-ultraviolet agent, anti-hydrolysis agent and pigment. In the present invention, the first mixing is preferably stirring and mixing, and the speed of the stirring and mixing is preferably 500-1400r / min, and in a specific embodiment, it can be 500r / min, 800r / min, 1000r / min, 1200r / min or 1400r / min; the time of the first mixing is preferably 8-10min, and in a specific embodiment, it can be 8min, 9min or 10min; the temperature of the first mixing is preferably room temperature; the bio-based sodium sulfonate, silicon material, dispersant and inorganic powder can be evenly dispersed by the first mixing. In the present invention, the temperature of the second mixing is preferably room temperature, the time of the second mixing is preferably 3-5min, and in a specific embodiment, it can be 3min, 4min or 5min; the second mixing is preferably stirring and mixing.
[0046] In the present invention, the temperature of the extrusion granulation is preferably 130-160°C, and in specific embodiments may be 130°C, 140°C, 150°C or 160°C.
[0047] The present invention also provides the use of the anti-scratch and light-shielding masterbatch described in the above technical solution or the anti-scratch and light-shielding masterbatch prepared by the preparation method described in the above technical solution as a filler. The anti-scratch and light-shielding masterbatch provided by the present invention has excellent anti-scratch and light-shielding effects, and has a good application prospect as a filler for polymer composite materials, especially a filler for polymer playing cards.
[0048] The present invention also provides a biodegradable composite material, which comprises the following raw materials, measured by weight: 50 to 75 parts of polylactic acid, 0 to 10 parts of polyhydroxyalkanoate, 5 to 20 parts of polycaprolactone, 5 to 10 parts of polybutylene succinate, 5 to 20 parts of anti-scratch and light-shielding masterbatch, 1 to 5 parts of antistatic agent, 0 to 2 parts of rare earth additive, and 0 to 5 parts of pigment; the anti-scratch and light-shielding masterbatch is the anti-scratch and light-shielding masterbatch described in the above technical scheme or the anti-scratch and light-shielding masterbatch prepared by the preparation method described in the above technical scheme.
[0049] The invention uses polylactic acid as a main raw material to provide basic hardness for the biodegradable composite material; adds polyhydroxyalkanoate to provide hardness and accelerate the degradation of polylactic acid after the material is used and discarded; adds polycaprolactone and polybutylene succinate to increase the flexibility and cold resistance of the anti-scratch and light-shielding masterbatch; improves the scratch resistance of the surface of the biodegradable composite material and adjusts the light-shielding property of the material through the anti-scratch and light-shielding masterbatch; adds an antistatic agent to reduce the generation of static electricity in the production of the biodegradable composite material and the static adsorption between sheets during printing; and adds a rare earth additive to help accelerate the shaping cycle of the biodegradable composite material during production and assist in improving the toughness of the biodegradable composite material.
[0050] In terms of mass fractions, the raw materials for preparing the biodegradable composite material provided by the present invention include 50 to 75 parts of polylactic acid (PLA), and in specific embodiments, it can be 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts or 75 parts. In the present invention, the number average molecular weight of the polylactic acid is preferably 150,000 to 300,000, and in specific embodiments, it can be 150,000, 180,000, 200,000, 220,000, 250,000, 280,000 or 300,000. In the present invention, the polylactic acid preferably includes at least one of high optical purity polylactic acid and medium and low optical purity polylactic acid; the polylactic acid preferably includes one or more of Total LX175, Total L175, Zhejiang Hisun 190 and Anhui Fengyuan 801, and more preferably Total LX175. The use of polylactic acid in the present invention can reduce the impact of self-crystallization on post-processing.
[0051] In terms of the mass fraction of the polylactic acid, the raw materials for preparing the biodegradable composite material provided by the present invention include 0 to 10 parts of polyhydroxyalkanoate (PHA), which can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 8.5, 9, 9.5 or 10 parts in a specific embodiment. In the present invention, the number average molecular weight of the polyhydroxyalkanoate is preferably 400,000 to 600,000, which can be 400,000, 450,000, 500,000, 550,000 or 600,000 in a specific embodiment. In the present invention, the polyhydroxyalkanoate includes one or more of poly-β-hydroxybutyric acid (PHB), poly 3-hydroxybutyrate / 4-hydroxybutyrate copolymer (P34HB), poly-β-hydroxybutyric acid hexanoate (PHBH) and poly 3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV).
[0052] In parts by mass, the raw materials for preparing the biodegradable composite material provided by the present invention include 5 to 20 parts of polycaprolactone (PCL), and in specific embodiments, it can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts or 20 parts. In the present invention, the number average molecular weight of the polycaprolactone is preferably 60,000 to 80,000, and in specific embodiments, it can be 60,000, 65,000, 70,000, 75,000 or 80,000.
[0053] In terms of mass fraction, the raw materials for preparing the biodegradable composite material provided by the present invention include 5 to 10 parts of polybutylene succinate (PBS), which may be 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10 parts in a specific embodiment. In the present invention, the number average molecular weight of the polybutylene succinate is preferably 200,000 to 300,000, which may be 200,000, 220,000, 250,000, 280,000 or 300,000 in a specific embodiment. In the present invention, the polybutylene succinate preferably includes one or more of Thailand FZ91PM / PB, Kingfa Technology A200 and Blue Mountain Tunhe TH804.
[0054] The raw materials for preparing the biodegradable composite material provided by the present invention include 5 to 20 parts of anti-scratch and light-shielding masterbatch by weight, and in specific embodiments, it can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts or 20 parts.
[0055] The raw materials for preparing the biodegradable composite material provided by the present invention include 1 to 5 parts of antistatic agent by weight, and in specific embodiments, it can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the antistatic agent preferably includes one or both of Sukarno S-546 and Sukarno DY2016.
[0056] In terms of mass fraction, the raw materials for preparing the biodegradable composite material provided by the present invention include 0 to 2 parts of rare earth additives, which may be 0 parts, 0.5 parts, 1 parts, 1.5 parts or 2 parts in specific embodiments. In the present invention, the rare earth additive preferably includes a lanthanide additive or a cerium additive, which may be Baotou Rare Earth Institute BRE-C-200 in specific embodiments. The present invention can improve the tensile strength of the material by adding a rare earth additive.
[0057] In terms of mass fraction, the raw materials for preparing the biodegradable composite material provided by the present invention include 0 to 5 parts of pigment, and in specific embodiments, it can be 0, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5 parts. In the present invention, the pigment preferably includes one or more of titanium dioxide, lithopone, zinc white and antimony white; the titanium dioxide is preferably rutile titanium dioxide.
[0058] The present invention also provides a method for preparing the biodegradable composite material described in the above technical solution, comprising the following steps: mixing the raw materials for preparation, and performing melt extrusion granulation to obtain the biodegradable composite material.
[0059] In the present invention, the mixing temperature is preferably room temperature, the mixing preferably includes stirring mixing, the stirring mixing speed is preferably 500-1400r / min, and in specific embodiments it can be 500r / min, 600r / min, 800r / min, 1000r / min, 1200r / min or 1400r / min; the mixing time is preferably 5-10min, and in specific embodiments it can be 5min, 6min, 7min, 8min, 9min or 10min; the mixing is preferably carried out in a high-speed mixer.
[0060] In the present invention, the melt extrusion granulation is preferably carried out in a twin-screw extruder. Specifically, the premix obtained by mixing is added to the twin-screw extruder through a feed port for melt extrusion granulation. In the present invention, the temperature of the melt extrusion granulation is preferably 165-200°C, and the temperature of the melt extrusion granulation is preferably divided into one to eight zones, and the temperatures of the one to eight zones are preferably 160-170°C, 175-185°C, 180-190°C, 185-195°C, 185-195°C, 185-195°C, 175-185°C, 165-175°C, and in a specific embodiment, the temperatures of the one to eight zones can be 165°C, 180°C, 185°C, 190°C, 190°C, 190°C, 180°C and 170°C. In the present invention, the particle size of the biodegradable composite material particles obtained by the melt extrusion granulation is preferably 2-3mm.
[0061] The present invention also provides the use of the biodegradable composite material described in the above technical solution or the biodegradable composite material prepared by the preparation method described in the above technical solution in the preparation of playing cards, packaging materials or disposable blister products. The biodegradable playing cards prepared using the biodegradable composite material provided by the present invention as a preparation raw material have excellent antibacterial and anti-mildew properties, are low-carbon and environmentally friendly, are not easy to curl and open, are waterproof and moisture-proof, are easy to print, have good color fastness, have the texture of traditional paper, are completely biodegradable after use, or can be made into a home compost material as needed, and can replace traditional paper playing cards and PVC plastic playing cards.
[0062] The present invention also provides a biodegradable playing card, which is made of the biodegradable composite material described in the above technical solution or the biodegradable composite material prepared by the preparation method described in the above technical solution.
[0063] The present invention also provides a method for preparing the biodegradable playing cards described in the above technical solution, comprising the following steps: mixing raw materials for preparing biodegradable composite materials, and sequentially performing sheet extrusion, stretching and shaping to obtain the biodegradable playing cards.
[0064] In the present invention, the temperature of sheet extrusion is preferably 160-200°C, and the temperature of sheet extrusion is preferably divided into one to eight zones, and the temperatures of the one to eight zones are preferably 160-170°C, 175-185°C, 180-190°C, 185-195°C, 185-195°C, 185-195°C, 175-185°C, 165-175°C, in sequence. In a specific embodiment, the temperatures of the one to eight zones may be 165°C, 180°C, 185°C, 190°C, 190°C, 190°C, 180°C and 170°C, in sequence; the sheet extrusion is preferably carried out in a sheet extruder.
[0065] In the present invention, the stretching speed is preferably 23-30 m / min, and in specific embodiments may be 23 m / min, 25 m / min, 28 m / min or 30 m / min.
[0066] In the present invention, after the stretching, the stretched composite material obtained by the stretching is preferably cooled. In the present invention, the cooling temperature is preferably 25 to 55°C, and in a specific embodiment, it can be 25°C, 30°C, 40°C, 50°C or 55°C; the cooling method preferably includes one or both of roller cooling and oven air cooling.
[0067] In the present invention, the shaping preferably includes baking shaping, and the baking shaping temperature is preferably 35-45°C, and in a specific embodiment can be 35°C, 40°C or 45°C.
[0068] In the present invention, after the shaping, the method preferably further comprises: subjecting the shaped composite material obtained by the shaping to corona treatment or not. The present invention does not specifically limit the conditions of the corona treatment, and the corona treatment conditions well known to those skilled in the art can be used. The present invention can improve the printing effect of the biodegradable playing cards by performing the corona treatment.
[0069] In the present invention, after the shaping, the present invention preferably further comprises: cutting into pieces, printing and cutting to obtain biodegradable playing cards.
[0070] The present invention directly prepares biodegradable playing cards by extruding, stretching and shaping the raw materials of the biodegradable composite material, has a simple preparation process, low processing cost, and can also reduce thermal decomposition caused by multiple processing of the biodegradable composite material.
[0071] To further illustrate the present invention, the anti-scratch shading masterbatch and its preparation method and application, the biodegradable composite material and its preparation method and application, and the biodegradable playing cards and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0072] In the following examples, the models of PBAT are Xinjiang Lanshan Tunhe TH801 (Example 1), Kingfa Technology A400 (Example 2) and BASF C1200 (Example 3). The particle size of the inorganic powder is ≤8μm. The antioxidant is antioxidant 1010: antioxidant 168 mass ratio = 1:1. The anti-ultraviolet agent is UV-3808. The model of bio-based sodium sulfonate is HG-600S. The polymerized polycarbodiimide is Shanghai Langyi 210. The titanium dioxide is rutile titanium dioxide.
[0073] The model of PLA is Total LX175. The model of PHB is PB3000G (Example 5), Beijing Weiguo; the model of P34HB is MDF1500 (Example 6), Zhuhai Maidefa. The number average molecular weight of PCL is 60,000 to 80,000. The models of PBS are Thailand FZ91PM / PB (Example 5), Kingfa Technology A200 (Example 7) and Blue Mountain Tunhe TH804 (Examples 4 and 6). The antistatic agent is Sukarno S-546 (Examples 4-5) and DY2016 (Examples 6-7). The rare earth additive is Baotou Rare Earth Institute BRE-C-200.
[0074] Activation of inorganic powder: Inorganic powder and 2% of the mass of KH550 coupling agent of the inorganic powder are stirred and activated at 500 r / min for 10 min in a high-speed mixer to obtain activated inorganic powder.
[0075] Examples 1 to 3
[0076] Preparation of Anti-scratch Light-shielding Masterbatch
[0077] The ingredients are prepared according to Table 1. Bio-based sodium sulfonate, potassium aluminum silicate, dispersant (ethylene bisstearamide) and activated inorganic powder (the types of inorganic powder are shown in Table 1) are stirred and mixed at room temperature and 1200 r / min for 8 minutes to obtain a mixture; the mixture, polybutylene terephthalate-adipate (PBAT), antioxidant, anti-ultraviolet agent (UV-3808) and anti-hydrolysis agent 210 are stirred and mixed at room temperature and 800 r / min for 5 minutes, and extruded and granulated at 140-150° C. to obtain an anti-scratch light-shielding masterbatch with a particle size of 2.5 mm.
[0078] Table 1 Raw materials for the preparation of anti-scratch light-shielding masterbatch in Examples 1 to 3 (parts by mass)
[0079] raw material Example 1 Example 2 Example 3 PBAT 29 27 25 Potassium aluminum silicate 5 16 10 Activated talc 54.5 / 40 Activated calcium carbonate / 40 10 Antioxidants 0.2 0.3 1 Ethylene bisstearamide 5 4 3 Anti-hydrolysis agent 210 3 5 4 UV protection agent 0.3 0.2 0.5 Titanium Dioxide 2 5 2.5 Bio-based sodium sulfonate 1 2.5 4
[0080] Embodiments 4 to 7
[0081] According to Table 2, PLA, PCL, PHA, rare earth additives, antistatic agents and anti-scratch light-shielding masterbatch were added to a high-speed mixer, stirred and mixed at room temperature and 500r / min for 5 minutes to obtain a premix; the premix was extruded in a sheet extruder, stretched at a speed of 30m / min, cooled at a roller temperature of 45°C, baked at 40°C for shaping, cut into pieces, printed, and cut to obtain biodegradable playing cards. Among them, the temperatures of zones 1 to 8 of the sheet extruder are 165°C, 180°C, 185°C, 190°C, 190°C, 190°C, 180°C and 170°C, respectively.
[0082] Figure 1 This is a physical picture of the whole set of biodegradable playing cards prepared in Example 4, Figure 1 It can be seen that the biodegradable playing cards prepared by the present invention are not easy to curl or open, are waterproof and moisture-proof, are easy to print, have good color fastness, and have the texture of traditional paper.
[0083] Comparative Example 1
[0084] Playing cards were prepared according to the methods of Examples 4 to 7, and the raw materials were as shown in Table 2.
[0085] Table 2 Raw materials for preparing playing cards (parts by mass)
[0086] Material Example 4 Example 5 Example 6 Example 7 Comparative Example 1 PLA 50 68 60 70 70 PCL 20 / 10 / PHA / 10 10 / PBS 10 5 10 6 30 Anti-scratch light-shielding masterbatch 19 15 5 20 Antistatic Agents 1 2 5 3 Rare earth additives / / / 1
[0087] Test Case
[0088] The playing cards prepared in Examples 4 to 7 and Comparative Example 1 were tested in accordance with QB / T 2228-2023 "Playing Cards" and GB6675.4-2014 "Toy Safety Part 4: Migration of Certain Elements", and the results are shown in Table 3.
[0089] Table 3 Performance test results of playing cards prepared in Examples 4 to 7 and Comparative Examples
[0090]
[0091] As shown in Table 3, since the comparative example 1 does not consider the special requirements such as anti-scratch and light shielding, the material is bright, easy to slip, relatively soft, with poor stiffness and elasticity close to the upper limit, which cannot meet the needs of subsequent product production. The biodegradable playing cards prepared by the present invention fully meet the production quality requirements and meet the requirements of the superior product inspection standards.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A scratch-resistant light-shielding masterbatch, comprising the following raw materials, by weight: 25 to 30 parts of polybutylene terephthalate-adipate, 40 to 80 parts of inorganic powder, 3 to 5 parts of dispersant, 0.2 to 1 part of antioxidant, 0.2 to 0.5 part of anti-ultraviolet agent, 5 to 16 parts of silicon material, 1 to 5 parts of bio-based sodium sulfonate, 3 to 5 parts of anti-hydrolysis agent, and 0 to 5 parts of pigment.
2. The anti-scratch light-shielding masterbatch according to claim 1, characterized in that: The number average molecular weight of the polybutylene terephthalate-adipate is 200,000 to 300,000; The inorganic powder includes one or more of talc, calcium carbonate, barium sulfate and silicon powder; the particle size of the inorganic powder is ≤8 μm; the inorganic powder is activated before use, and the activation reagent used for the activation includes at least one of a coupling agent and stearic acid; The dispersant includes one or more of oleamide, erucamide and ethylenebisstearamide; The antioxidant includes one or more of phenolic antioxidants, amine antioxidants and phosphite antioxidants; The silicon material includes at least one of ultra-high molecular weight organic silicon and potassium aluminum silicate; The anti-hydrolysis agent includes at least one of monomeric polycarbodiimide and polymeric polycarbodiimide.
3. The method for preparing the anti-scratch light-shielding masterbatch according to any one of claims 1 to 2, comprising the following steps: The prepared raw materials are mixed and then extruded and granulated to obtain the anti-scratch light-shielding masterbatch.
4. Use of the anti-scratch and light-shielding masterbatch according to any one of claims 1 to 2 or the anti-scratch and light-shielding masterbatch prepared by the preparation method according to claim 3 as a filler.
5. A biodegradable composite material, characterized in that: The preparation method comprises the following raw materials, in parts by mass: 50-75 parts of polylactic acid, 0-10 parts of polyhydroxyalkanoate, 5-20 parts of polycaprolactone, 5-10 parts of polybutylene succinate, 5-20 parts of anti-scratch and sunshade masterbatch, 1-5 parts of antistatic agent, 0-2 parts of rare earth additive, and 0-5 parts of pigment; the anti-scratch and sunshade masterbatch is the anti-scratch and sunshade masterbatch described in any one of claims 1 to 2 or the anti-scratch and sunshade masterbatch prepared by the preparation method described in claim 3.
6. The biodegradable composite material according to claim 5, characterized in that: The rare earth additive includes a lanthanide additive or a cerium additive; The number average molecular weight of the polylactic acid is 150,000 to 300,000; The number average molecular weight of the polycaprolactone is 60,000 to 80,000; The number average molecular weight of the polybutylene succinate is 200,000 to 300,000; The number average molecular weight of the polyhydroxyalkanoate is 400,000 to 600,000; The polyhydroxyalkanoate includes one or more of poly-β-hydroxybutyric acid, poly 3-hydroxybutyrate / 4-hydroxybutyrate copolymer, poly-β-hydroxybutyric acid hexanoate and poly 3-hydroxybutyrate-co-3-hydroxyvalerate.
7. The method for preparing the biodegradable composite material according to claim 5 or 6, characterized in that: The following steps are involved: The prepared raw materials are mixed, melt-extruded and granulated to obtain a biodegradable composite material.
8. Use of the biodegradable composite material according to any one of claims 5 to 6 or the biodegradable composite material prepared by the preparation method according to claim 7 in the preparation of playing cards, packaging materials or disposable blister products.
9. A biodegradable playing card, made of the biodegradable composite material according to any one of claims 5 to 6 or the biodegradable composite material prepared by the preparation method according to claim 7.
10. The method for preparing the biodegradable playing cards according to claim 9, comprising the following steps: The raw materials for preparing the biodegradable composite material are mixed, and the sheet is extruded, stretched and shaped in sequence to obtain the biodegradable playing cards.